PENGEMBANGAN e-LKPD IPA MATERI SISTEM PENCERNAAN BERBASIS PROBLEM-BASED LEARNING (PBL) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK KELAS V SEKOLAH DASAR - Valensia, Realita; Widi Winarni, Endang; Muktadir, Abdul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to develop, evaluate the feasibility, determine user responses, and examine the effectiveness of a Problem-Based Learning (PBL)-based electronic student worksheet (e-LKPD) on the human digestive system to improve the critical thinking skills of fifth-grade elementary school students. The study employed a Research and Development (R&D) method using the ADDIE model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects included material experts, language experts, graphic design experts, fifth-grade teachers, and fifth-grade students of SDN 20 Bengkulu Tengah. Data were collected through validation sheets, teacher and student response questionnaires, and critical thinking tests administered as pretests and posttests. The developed e-LKPD consisted of a title, learning instructions, learning outcomes, human digestive system materials, supporting information, problem-based tasks, and critical thinking assessments. The validation results indicated that the e-LKPD had an excellent level of feasibility, with Aiken’s V values of 1.00 for the material and graphic aspects (very valid) and 0.50–0.67 for the language aspect (valid). Reliability testing showed an agreement percentage of 100% for the material and graphic aspects and 60% for the language aspect. Teacher and student responses were categorized as good, indicating that the e-LKPD was practical for classroom use. The effectiveness test results showed an increase in students’ average scores from 68 in the pretest to 80 in the posttest, with an N-Gain score of 0.38, which falls into the moderate category. Therefore, the developed PBL-based science e-LKPD was found to be valid, practical, and effective in improving the critical thinking skills of fifth-grade elementary school students.